2012
DOI: 10.1039/c2ob26022k
|View full text |Cite
|
Sign up to set email alerts
|

A subnanomolar fluorescent probe for protein kinase CK2 interaction studies

Abstract: Up-regulation of an acidophilic protein kinase, CK2, has been established in several types of cancer. This cognition has made CK2 an important target for drug development for cancer chemotherapy. The characterization of potential drug candidates, determination of the structure and clarification of the functions of CK2 could be facilitated by the application of small-molecule fluorescent probes that bind to the active site of the enzyme with high affinity and selectivity. We have used a bisubstrate approach for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…Second, it possesses remarkable affinity toward CK2, and its cellular activity hasb een demonstrated. First, the oligo-aspartate moiety present in previously reported compounds [18,19] was replaced with the corresponding carboxylate-rich peptoid chain comprising N-carboxymethylglycine (iminodiacetic acid, Ida) residues. ATBi se xpected to give two essential polar interactions with the ATPp ocket of CK2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it possesses remarkable affinity toward CK2, and its cellular activity hasb een demonstrated. First, the oligo-aspartate moiety present in previously reported compounds [18,19] was replaced with the corresponding carboxylate-rich peptoid chain comprising N-carboxymethylglycine (iminodiacetic acid, Ida) residues. ATBi se xpected to give two essential polar interactions with the ATPp ocket of CK2.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20] Both good cellular accumulation and appropriate intracellular compartmentalization are criticalf actorsf or as uccessful PK-inhibitor-based drug. CX-4945, the only ATP-competitive CK2 inhibitor that has reached clinicalt rials, is the mosts uccessful example.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of CK2 (Protein Data Bank code 4FBX) was used to determine the best docking position for rifampin at the binding site (27). The structure of rifampin was obtained from another Protein Data Bank structure (entry 2HW2) (28).…”
Section: Methodsmentioning
confidence: 99%
“…[33,34,[36][37][38][39]). A comparison of the IC 50 values within this group showed that only CK2a and CK2a 0 exhibit values below 10 nM.…”
mentioning
confidence: 97%